Ranking and Matchmaking - Graepel, Thore; Herbrich, Ralf (Game Developer Magazine, 2006)
Online game modes are gradually becoming the standard for console games, rather than an added bonus. But how do you get the right players playing against the right people, close enough in skill to be challenging, but not so difficult as to be frustrating?